Dalil Hukum Perkawinan Beda Agama - Ahmad Zaky Nauval; Mhd. Amar Adly; Heri Firmansyah (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Marriage is not only about forming a family that occurs because of the union of a man and a woman, but marriage is an innate bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the One Godhead. It is a problem if marriage is the desire of each prospective couple but is hindered due to religious differences, In practice interfaith marriage is not a new thing and has caused many pros and cons in the community. This paper aims to find out the legal postulates of interfaith marriage both in terms of Islamic law and positive law in Indonesia. Using juridical-normative legal research methods, this article will review these contradictions. The results of the study show that interfaith marriage, both in terms of Islamic law and positive law, is prohibited.